Single-Phase induction motor performance with Symmetrical AC supply - Muhammad Sukri Ngatiman (Universiti Malaysia Perlis, 2009)
One source of distortion is represented by non-linear loads. When a pure fundamental voltage with zero source impedance is applied to a non linear load, the resulting current differs in shape from the applied voltage. The growing use of power electronic applications has increased the friction of non-sinusoidal currents and voltages in utility networks, drives equipments and building. If a thyristor switch is connected between ac supply and load, the power flow can be controlled by varying the rms value of AC voltage applied to the load; and this type of power circuit is known as an AC voltage controller. The most common applications of AC voltage controllers have increased the friction of non-sinusoidal currents and voltages in utility networks, drives equipments and building. In this project, the symmetrical AC voltage is found from the output of a symmetrical AC voltage controller, therefore, the output is not pure sinusoidal. For comparative need of single phase induction motor performance, the motor is the subjected to this output voltage, and also with pure sinusoidal input voltage. The performances are illustrated in term of speed of motor, harmonics, power factor and power consumption on input source side view.